Cost-effectiveness analysis of Chlamydia trachomatis screening in Dutch pregnant women. (16th November 2016) - Rours, G. I. J. G.; Smith-Norowitz, Tamar Anne; Ditkowsky, Jared; Hammerschlag, Margaret R.; Verkooyen, R. P.; de Groot, R.; Verbrugh, H. A.; Postma, M. J.
Abstract : Chlamydia trachomatis infections during pregnancy may have serious consequences for women and their offspring. Chlamydial infections are largely asymptomatic. Hence, prevention is based on screening. The objective of this study was to estimate the cost-effectiveness of C. trachomatis screening during pregnancy. We used a health-economic decision analysis model, which included potential health outcomes of C. trachomatis infection for women, partners and infants, and premature delivery. We estimated the cost-effectiveness from a societal perspective using recent prevalence data from a population-based prospective cohort study among pregnant women in the Netherlands. We calculated the averted costs by linking health outcomes with health care costs and productivity losses. Cost-effectiveness was expressed as net costs per major outcome prevented and was estimated in base-case analysis, sensitivity, and scenario analysis. In the base-case analysis, the costs to detect 1000 pregnant women with C. trachomatis were estimated at €527, 900. Prevention of adverse health outcomes averted €626, 800 in medical costs, resulting in net cost savings. Sensitivity analysis showed that net cost savings remained with test costs up to €22 (test price €19) for a broad range of variation in underlying assumptions. Scenario analysis showed even more cost savings with targeted screening for women less than 30 years of age or with first pregnancies only. Antenatal screening for C. trachomatis is a cost-saving intervention when testing all pregnant women in the Netherlands. Savings increase even further when testing women younger than 30 years of age or with pregnancies only.